2016
DOI: 10.1507/endocrj.ej16-0078
|View full text |Cite
|
Sign up to set email alerts
|

Reduced circulating oxytocin and High-Molecular-Weight adiponectin are risk factors for metabolic syndrome

Abstract: The neurohypophysial hormone, oxytocin, is involved in the regulation of energy metabolism. Adiponectin (APN) is an adipose tissue-specific serum protein that inversely associates with metabolic syndrome (MetS). High-molecular-weight adiponectin (HMW APN) is considered the active form. In the present study, we aimed to determine the relationships of oxytocin and HMW APN to MetS and investigate whether or not the combination of oxytocin and HMW APN is associated with further metabolic abnormalities compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
1
22
1
Order By: Relevance
“…In contrast, we found no significant relationship between lipid levels and oxytocin or irisin levels. Very recently, Yuan et al (17) demonstrated that patients with MS had significantly lower oxytocin levels than did patients without MS, which is consistent with our findings. These reports suggest that pro-inflammatory cytokines may be a key factor in the ability of oxytocin to suppress the inflammation seen in MS.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast, we found no significant relationship between lipid levels and oxytocin or irisin levels. Very recently, Yuan et al (17) demonstrated that patients with MS had significantly lower oxytocin levels than did patients without MS, which is consistent with our findings. These reports suggest that pro-inflammatory cytokines may be a key factor in the ability of oxytocin to suppress the inflammation seen in MS.…”
Section: Discussionsupporting
confidence: 93%
“…Few studies have been performed to determine the circulating levels of oxytocin in obese adults (14,15,16,17,42). Conflicting findings exist regarding whether oxytocin levels are increased (42), unchanged (43), or decreased (16,17) in obese adults. Variable sample sizes and different study techniques might be the causes of these differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent article reported that circulating oxytocin levels are decreased in obesity and type 2 diabetic patients [138,139], HFD-induced obese mice [25], and Zucker fatty rats [38]. This decrease in plasma oxytocin levels may be a result of severe obesity since significant plasma oxytocin degradation was not confirmed in the studies using obese models fed HFD for 8-16 weeks [28,39].…”
Section: Clinical Implications Of Oxytocinmentioning
confidence: 99%
“…Adiponectin suppresses glucose production in the liver and enhances fatty acid oxidation in skeletal muscle, resulting in beneficial metabolic sequelae [25]. Adiponectin levels have been shown to be significantly reduced in obesity [26]. With regards to chronic inflammation processes, this peptide is inversely associated with CRP levels independently of all other MeS factors [27].…”
Section: Cardiovascular Systemmentioning
confidence: 99%